Ultrassonografia versus eletroneuromiografia para o diagnóstico de fasciculação na esclerose lateral amiotrófica: revisão sistemática e metanálise - Duarte, Marcio Luis [UNIFESP] (2018)
Introduction: Fasciculations are rapid, random, fine, flickering, or vermicular twitching movements of a group of muscle fibres innervated by a single motor unit – is almost obligatory among patients with amyotrophic lateral sclerosis which is the most common motor neuron disease in adults on the planet – and can be diagnosed by clinical evaluation, by electromyography (EMG) or by ultrasonography (US). There is uncertainty as to which of the diagnostic methods is best in the evaluation of fasciculations. Objective: To determine the diagnostic accuracy of the US and EMG for the diagnosis of fasciculation and to compare its detection rates. Determine which of these two diagnostic methods is best for the diagnosis of fasciculation, as well as which is the best muscle to be evaluated in each method. Methodology: We searched the electronic databases Cochrane Library, MEDLINE, EMBASE and LILACS from 12/01/2016 to 12/12/2017, as well as the reference lists of the included studies and the main revisions on the subject, for studies evaluating the diagnostic accuracy and detection rates of the US and EMG for the diagnosis of fasciculation, independently of the status of the publication and the language, selecting 10 studies at the end of the QUADAS 2 and RTI item bank methodological quality evaluation. Results: It was observed that the US, both 10 seconds and 30 seconds, had a detection rate higher than EMG in all muscles evaluated, as well as patients, with emphasis on the 30second evaluation of the brachial biceps muscle – 88% – and tibialis anterior muscle – 82%. The EMG, in these muscles, had a detection rate of 61% and 47%, respectively. The evaluation of the detection rate by patients did not present a significant difference between the US of 10 and 30 seconds – 92% and 93% respectively. The accuracy of the US of 10 seconds in the muscles is of 70%, whereas in the patients it is of 85%. In the US of 30 seconds, the accuracy in the patients is of 82%. The accuracy of the EMG was not possible because the studies that evaluated it did not perform the evaluation with the control group. Conclusion: The US presented detection rates superior to EMG, independently of the time of its evaluation and of the evaluated muscles, being, therefore, a better diagnostic method for the evaluation of the fasciculation.